2019
DOI: 10.1108/qram-02-2018-0017
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of target cost management in a non-Japanese environment

Abstract: Purpose Drawing from dynamic capability theory, this paper aims to examine the implementation of target cost management (TCM) in a non-Japanese environment. Design/methodology/approach Based on a case study at Company ABC, an automotive manufacturer in Malaysia, this paper investigates the differences in the TCM implementation process between Company ABC and companies operating in the Japanese business environment. The data were collected through in-depth interviews, direct observation and document reviews. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…With respect to the use of case study method, the review found an extensive focus on the development of model (Englund and Gerdin, 2014; Barros and Ferreira, 2017; Cooper et al , 2017) and implementation process of a particular SMA technique (Herath et al , 2014; Cooper et al , 2019; Baharudin and Jusoh, 2019) in a particular organizational setting.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…With respect to the use of case study method, the review found an extensive focus on the development of model (Englund and Gerdin, 2014; Barros and Ferreira, 2017; Cooper et al , 2017) and implementation process of a particular SMA technique (Herath et al , 2014; Cooper et al , 2019; Baharudin and Jusoh, 2019) in a particular organizational setting.…”
Section: Resultsmentioning
confidence: 99%
“…Woods et al (2012), using a case study of MNC, documented how economic value added is introduced in TC system and provided preliminary evidence on how TC can, while using with other SMA techniques, play the bridging role in connecting strategic process and profit generation. Baharudin and Jusoh (2019) demonstrated how a non-Japanese company (Malaysian automotive manufacturer) modified the fundamental steps of TCM to match with its resources, processes and strategic routines.…”
Section: Results Of Previous Researchmentioning
confidence: 99%
“…It is possible to think of target costing as a cost management system that focuses on price, customer, and project by incorporating various organizational functions (Abd; Jasim, 2019; Mao; Chen, 2021; Toosi; Chamikarpour, 2021). Its main objective is to adjust the operating cost of a product, i.e., a good or a service, to determine the target price and desired margins in the context of the company's strategic planning (Baharudin;Jusoh, 2019;Homburg et al, 2021a).…”
Section: Target Costingmentioning
confidence: 99%
“…In fact, the achievement of Malaysia's automotive industry had attracted researchers to investigate relevant areas within the industry. For instance, works in the following research areas are worth mentioning like Quality Practices (Habidin et al, 2018;Habidin & Mohd Yusof, 2013;Mohd et al, 2011), Accounting and Costing (Baharudin & Jusoh, 2019) and Business Strategies (Nazir & Shavarebi, 2019).…”
Section: The Automotive Industry In Malaysiamentioning
confidence: 99%